Characteristics of hospitalized patients prescribed oral nutrition supplements in Thailand: A cross-sectional nutrition day survey. (October 2019) - Rattanachaiwong, Sornwichate; Warodomwichit, Daruneewan; Yamwong, Preyanuj; Keawtanom, Songsri; Hiesmayr, Michael; Sulz, Isabella; Singer, Pierre
Summary: Background and objectives: Despite the proven benefits of oral nutrition supplements (ONS), its prescription in Thailand are far less than it should mainly due to limitation of reimbursement. Our aim was to compare hospital outcomes between hospitalized patients receiving only hospital food to those receiving hospital food with ONS. Methods and study design: An annual cross-sectional survey, NutritionDay (nD), in Thailand was conducted in 2 hospitals from 2010 to 2015. The hospital outcomes were followed at day 30 after first evaluation. Logistic regression and Cox regression were performed to compare outcome between groups. Results: 524 hospitalized patients, 472 with only hospital food and 52 with ONS, were included. Patients with ONS had longer hospital stay prior to recruitment, reported more physical dependencies, and ate less food. The ONS group was less likely to be discharged within 30 days as compared to hospital food group (unadjusted OR 0.28, 95% CI 0.16–0.52) but this effect was not significant after adjustment for length of stay before nD and PANDORA score (adjusted OR 0.62, 95% CI 0.3–1.34). Cox regression showed a trend to decreased rate of discharge within 30 days in the ONS group. Conclusions: This cross-sectional study showed a trend of worse outcomes associated with ONS prescription which might be related with higher mortality risk according to PANDORA score and longer previous hospital stay of the patients in the ONS group. Since the 2 studied groups were not comparable, further studies in this specific population should be performed.